Exploration of Easy Ways to use Green Screen in Making Learning Videos in Information Technology Education Study Programs - Amir, Day Ramadhani; Ulfia, Nadif; Muktamir, Muktamir (Jurnal Pendidikan Edutama, 2024)
This research aims to find an easy way to use green screens in making learning videos to make it easier for educators to convey learning. This type of research uses qualitative descriptive research. This research took data from lecturers or teachers at IKIP PGRI Bojonegoro. Data analysis through data collection through interviews and observations to the practice of making learning videos using a green screen. Learning video making activities use the video making stages from pre-production from story idea, synopsis, treatment script and full script. The production stage is the process of recording learning videos using a green screen background and collecting data in the form of images and writing. The third stage of post-production includes the editing stage, where the videos that have been taken are put together and everything that doesn't need to be removed by also editing the background using greenscreen to become the desired background.